Theory of Mind and social functioning in schizophrenia: correlation with figurative language abnormalities, clinical symptoms and general intelligence - Piovan, Cristiano; Gava, Laura; Campeol, Mara (Rivista di psichiatria, 2016)
Over past few decades, studies displayed Theory of Mind (ToM) as a system, including cognitive and affective features, rather than an unitary process. Within domains defining social cognition, ToM stands for the best predictor of poor social functioning in schizophrenia. The current study aimed to explore competence in ToM tasks, in metaphorical and idiomatic language identification tasks and in a conversational rules observance test, as well as relationship with social functioning, in a group of outpatients suffering from schizophrenia. METHODS.: 30 outpatients diagnosed with schizophrenia and 24 healthy subjects have been recruited. Both groups underwent TIB as premorbid IQ evaluation, PANSS, Theory of Mind Picture Sequencing Task, a metaphors and idiomatic expressions comprehension test and a conversational test. Social functioning was assessed with PSP. Results.Mean values of premorbid IQ showed no significant difference between patients and control group. In ToM and pragmatic competence tasks, differences between groups resulted in high significance, due to patients' lower performance. A correlation between metaphors and idiomatic expressions comprehension and second order false beliefs was detected. PSP showed a correlation with PANSS and cognitive-ToM, whereas leaving aside affective-ToM. Results showed how people affected with schizophrenia, in stable clinical condition, do have clear impairments in ToM and figurative language comprehension assignments. In our theoretical framework, correlation arisen between cognitive-ToM, pragmatic deficits, clinical status and social functioning level suggests usefulness of rehabilitative interventions to recover metacognitive functions and pragmatic abilities, in order to reduce social disability in schizophrenia.